Unified brand strategy and operation quality of business group: evidence from stock price crash risk - Cheng Zhang; Qingsheng Zeng; Qinwen Wu (China Journal of Accounting Studies)
Under the framework of a reputation governance mechanism, this paper analyzes how the unified brand strategy (UBS) impacts the operation quality of business groups. Evidence indicates that a higher degree of brand unity reduces the stock price crash risk, thereby enhancing operational quality. Cross-sectional analysis further supports the reputation theory, showing that the negative correlation between UBS and stock price crash risk is significant when the group receives high professional attention and has a strong brand reputation. The study also finds that UBS improves earnings quality, profitability, and earnings sustainability, further boosting operational quality. These findings provide important guidance for China’s rapid and stable development of the brand economy and the construction of a unified national market.